Molecular Magnetism of Lanthanides Complexes and Networks - Kevin Bernot (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Over the last ten years a fresh air has been blowing in the field of molecular magnetism with the re-introduction of lanthanides ions as spin carriers in magnetic molecules. The strong magnetic moment and huge magnetic anisotropy of lanthanide ions has enabled significant breakthroughs in magnetic blocking temperature and related phenomena. The chemical versatility of these ions is also a strong asset as easy substitution among the lanthanides series enables isotropic, anisotropic or solid-solutions of magnetic molecules. Additionally, their outstanding luminescent properties are key features in rationalizing the single-molecule magnet (SMM) behavior and paving the way toward production of multifunctional materials. In this book, selected examples of research on molecular magnetism of lanthanides complexes and networks are presented illustrating the current dynamism of this research field.